The Effect of Corruption on Public Financial Management System in Nigeria - John, Achanya Julius; Luma, Varzoa (Kashere Journal of Politics and International Relations, 2025)
The target of Nigeria reforming public financial management (PFM) system over the years was to reap the associated reward of financial propriety with the attendant socio-economic development. However, corruption in PFM system remains a serious problem in Nigeria. To examine this concern, the paper deployed information derived from official documents and extant literature to analyze the effect of corruption on PFM system in Nigeria. The analysis is anchored on the institutional theory and largely based on round 1 and 2 versions of the mapping and scoping surveys of anti-corruption and governance measures in PFM reports on Nigeria. Findings reveal that the effect of corruption is deep and substantial in PFM system in Nigeria. Effects include but not limited to distortion of public finance and procurement processes, payment systems, accounting, financial reporting and auditing systems. This stems from low adherence to laws and near absence of deterrence. The paper therefore recommends the criminalization of certain acts and omissions, as well as the development of a strong and compelling enforcement mechanism consisting of effective detection and diligent investigation, efficient prosecution, speedy adjudication and effective sanctions for culpable parties to serve as deterrent to violators of PFM laws in Nigeria.